A single‐ and multiple‐ascending dose study to evaluate the safety and pharmacokinetics of oral PU‐AD, an epichaperome inhibitor to treat Alzheimer's disease: Human/Trial design. (7th December 2020) - Silverman, Michael; Wallner, Barbara; Key, Cassandra; Duggan, Susan M.; Reynolds, Laurie
Abstract: Background: Breakdown of regulatory pathways designed to prevent aggregation and accumulation of disease‐associated proteins contributes to or causes Alzheimer's Disease (AD). Under these conditions epichaperomes form and take control of pathological pathways. PU‐AD is a small‐molecule, orally bioavailable inhibitor specific to epichaperomes with little or no effect on normal cells, and has shown dramatic beneficial effects in animal models of AD. We describe the first‐in‐man trial of PU‐AD. Objectives: This Phase 1, double‐blind, placebo‐controlled, single and multiple‐ascending dose study evaluated the safety and pharmacokinetics (PK) of single and multiple doses of oral PU‐AD. Methods: Cohorts of 8 subjects were randomly assigned to active treatment or placebo in a 6:2 ratio. Single doses of oral PU‐AD were 10 mg, 20 mg, and 30 mg in healthy subjects ages 18‐60 years, and daily doses of 20 mg and 30 mg daily for 7 days in healthy subjects >59 years old. Safety was evaluated through observation of adverse event incidence and severity; and changes from baseline in clinical laboratory test results, vital signs, physical examinations, or electrocardiogram results. Plasma PK parameters of PU‐AD were determined, and cerebrospinal fluid (CSF) was sampled for PU‐AD concentration and for biomarkers of neurodegenerative disease in the multiple‐dose cohorts. Results: PU‐AD was well‐tolerated, with an adverse event profile comparable to that of placebo. No adverse events were serious, severe, or led to withdrawal of dosing. Additionally, there were no other clinically significant safety findings to report. PK was dose‐proportional between 10 mg to 30 mg and showed minimal accumulation with repeated dosing. CSF analyses will be presented. Conclusion: PU‐AD, a novel and selective epichaperome inhibitor shown to be efficacious in animal AD models, warrants further evaluation in an AD population. This first‐in‐man trial demonstrated that PU‐AD is well‐tolerated, has favorable plasma PK and CSF exposure, and is a candidate for advancement into Phase 2A trials in AD populations to evaluate target engagement and pharmacological effects.